A Hybrid Access Method for Bibliographic Records - Bookstein, Abraham (Information Technology and Libraries, 1974)
This paper defines an access method for bibliographic records that combines features of the search key approach and the inverted file approach. It is a refinement of the search key technique that permits its extension to large files. A method by which this approach can be efficiently implemented is suggested.